Lauric acid saponified with calcium ameliorates indices of intestinal function and gut health in weaned piglets. Issue 1 (1st January 2021) - Rebucci, Raffaella; Comi, Marcello; Ghiringhelli, Matteo; Giorgi, Silvia; Cheli, Federica; Bontempo, Valentino
Abstract: Reducing the use of antibiotics is one of the largest challenges for pig production. The scientific community has investigated numerous alternative substances to antibiotics, including medium-chain fatty acids, due to their antimicrobial and protective effects on the gut health of piglets. The present study investigated the effect of lauric acid saponified with calcium (C12-Ca) on the growth performance and gut health parameters in post-weaning piglets. A total of 192 24-day-old piglets were assigned to one of three dietary treatments: CTR (basal diet alone), ANT (amoxicillin, 400 mg/kg) as a positive control diet, or C12-Ca (1 g/kg) for 28 days. C12-Ca did not affect performance, except for feed efficiency (FE), which increased ( p  < .05) in the C12-Ca and ANT groups from 15 to 28 days. On days 0 to 28, FE was higher ( p  < .001) in the C12-Ca group than in the CTR group. In the C12-Ca and CTR groups, antibiotic treatments against diarrhoea were reduced. A greater concentration of lactic acid was found in the small intestine in the C12-Ca group and the acetic acid concentration in the caecum decreased under C12-Ca treatment ( p  < .001). No differences in IL-10, IL-6, IgA, and IgG were found in faecal samples. In the duodenum and ileum, C12-Ca administration provided a higher total antioxidant capacity and lower malondialdehyde level ( p  < .001). C12-Ca improved the ileal villus height and width ( p  < .001). Our findings suggest that C12-Ca administration ameliorates the indices of intestinal function and gut health in weaned piglets. Highlights: Reducing the use of antibiotics is one of the largest challenges for pig production. Medium-chain fatty acids are important alternative substances to antibiotics. Lauric acid saponified with calcium represents a promising nutritional strategy for improving piglet gut health.